Evidence of Pilates practice on mental health of healthy people - Boix Vilella, Salvador; León Zarceño, Eva; Serrano Rosa, Miguel Ángel (Universidad y Salud, 2017)
Introduction: The Pilates method was designed to create a connection between mind and body through a combined work of strength and flexibility, without submitting the body to excessive stress. Objective: To expose the most relevant research results from an analytical-interpretative perspective, in relation to the mental health of healthy people who habitually practice Pilates. Materials and methods: An analysis of the main benefits of the Pilates method on mental health was carried out, by using the results of finished research. To do this, the databases ScienceDirect, PubMed and Dialnet were accessed to identify publications that relate Pilates to mental variables. Results: The 19 revised studies show scientific evidence on the levels of humor, self-efficacy, self-esteem, mood, stress, quality of sleep, depression and identification with physical exercise. However, studies focused on attention, anxiety-state, positive or negative affect and quality of life proved that the evidence is still very limited. Conclusions: New longitudinal cutting researches using sufficiently wide samples are necessary to clear the unknowns still existing in relation to Pilates. This will determine whether the high popularity of the method is associated with the important health benefits reported.